Homologous And Hetrologous Transplantation Of Bovine Ethmoid Carcinoma Cells - Ajith Jacob George (Centre of Excellence in Pathology, College of Veterinary and Animal Sciences, 1994)
Homologous and heterologous transplantation of bovine ethmoid carcinoma cells were attempted to assess the xenograftic efficiency of the neoplasm. Tumour tissue for the study was obtained from seven clinically affected cows. Histopathologically the tumours were classified as adenocarcinoma, papillary adenocarcinoma, undifferentiated carcinoma and squamous cell carcinoma. Tumour tissue/cell culture was successfully carried out using trypsinised single cell suspension and tumour tissue gragments. Calves were used as homologous hosts and rats, mice and rabbits were used as heterologous hosts. Cyclophosphamide, hydrocortisone and cyclosporine A were used as immunosuppressants. Transplantation was carried out subcutaneously or intraperitoneally. The inoculum consisted of trypsinised single cell suspension, tumour tissue fragments and cell suspension from tissue culture. Neoplastic cells failed to grow in immunosuppressed calves, rats and rabbits. Whereas, the tumour cells obtained by trypsinisation were successfully transplanted in mice immunosuppressed with cyclosporine A. The tumour growth was evident from the second week onwards. In immunosuppressed animals the total leucocyte count, differential leuocyte count and alphanapthyl acetate esterase positive lymphocyte count were very low compared to their controls. The results of the present study indicated that mice could be used as an experimental model for the studies on bovine ethmoid carcinoma.